Mekanisme E-Voting dalam Pemilihan Kepala Desa - Suleman, Zulfikri; Hendarso, Yoyok; Isyanawulan, Gita; Adyatma, Ryan Trisna (Jurnal Analisis Sosial Politik, 2018)
Election of village heads (pilkades) through the e-voting mechanism is a new thing in Indonesia, only held since 2013 and so far only covers 526 villages out of 70 thousand villages throughout Indonesia. The introduction of advanced technology in this pilkades has also raised several new aspects, one of which is the response and participation of the community, an important topic because it is directly related to the ongoing democratization process. This paper wants to reveal a description of the responses, interests and community participation in the village head elections in Biyuku village, Soak Tapeh sub-district and villages of Sukaraja Baru and Terentang, Bayuasin III sub-district, all in South Sumatra Province, which was held on November 16, 2017. Data for qualitative research on this topic was collected through in-depth interviews with relevant parties (village officials, electoral committees, community members) and literature review. The results of data analysis showed that the general public welcomed with enthusiasm the use of e-voting mechanisms in the organization of this pilkades. In line with this, the level of voter participation in voting has also increased sharply, for the village of Biyuku reaching 77% compared to only about 60% in pilkades with conventional mechanisms. It's just that it hasn't been revealed yet, the use of e-voting in this pilkades has increased community political participation in a substantive way. Thus, the Government through the Ministry of Communication and Information as well as the Village Community Development Agency / Agency at the regional government level need to broaden the scope and strengthen the quality of the use of e-voting mechanisms in the pilkades in this country, in accordance with the expectations of the community. Pemilihan kepala desa (pilkades) melalui mekanisme e-voting merupakan hal yang baru di Indonesia, baru dilaksanakan sejak tahun 2013 dan sejauh ini baru mencakup 526 desa dari 70 ribu desa di seluruh Indonesia. Pengenalan teknologi maju dalam pilkades ini juga telah memunculkan beberapa aspek baru yang salah satu di antaranya adalah tanggapan dan partisipasi masyarakat, satu topik penting karena terkait langsung dengan proses demokratisasi yang sedang berlangsung. Tulisan ini ingin mengungkapkan gambaran tentang tanggapan, minat dan partisipasi masyarakat dalam pilkades di desa Biyuku, Kecamatan Soak Tapeh dan desa-desa Sukaraja Baru dan Terentang, Kecamatan Bayuasin III, semuanya di Provinsi Sumatera Selatan, yang dilaksanakan tanggal 16 November 2017 yang lalu. Data untuk penelitian kualitatif tentang topik ini dikumpulkan melalui wawancara mendalam dengan pihak-pihak terkait (perangkat desa, panitia pemilihan, anggota masyarakat) serta kajian kepustakaan. Hasil analisis data menunjukkan, masyarakat secara umum menyambut dengan antusias penggunaan mekanisme e-voting dalam penyelenggaraan pilkades ini. Seturut dengan ini, tingkat partisipasi pemilih dalam pemberian suara juga meningkat tajam, untuk desa Biyuku mencapai 77% berbanding dengan hanya sekitar 60% dalam pilkades dengan mekanisme konvensional. Hanya saja memang belum terungkap, penggunaan e-voting dalam pilkades ini telah meningkatkan partisipasi politik masyarakat secara substantif. Dengan demikian, Pemerintah melalui Kementerian Komunikasi dan Informasi serta Dinas/Badan Pembangunan Masyarakat Desa di tingkat pemerintahan daerah perlu memperluas cakupan dan lebih memantapkan kualitas penggunaan mekanisme e-voting dalam pilkades di negeri ini, sesuai dengan harapan masyarakat.